Psychophysics Behavior of Human Tactile Mechanism to Discriminate Extremely Thin Copper Foils. - Azzeim Bin Mat Jusoh, Mohammad; Ohka, Masahiro; Miyaoka, Tetsu; Bin Che Abdullah, Sukarnur; Bin Hashim, Hafizan (International Journal of Engineering and Technology, 2018)
In this study, our objective is to analyze human tactile mechanism behavior in recognizing extremely thin foils using the psychophysics method. Seven pairs of copper foils ranging in thickness from 20 ~ 150 Î¼m were used in the experiment. We applied the method of constant stimuli to define the difference threshold between the materials. In order to increase the detection rate, contact between human tactile function and the metal foils was maintained. As a result, the Weber fraction c consistently reduces as thickness increases. However, the slope decrement is steep compared to previous experimentation (using stainless steel as base). We also validated the behavior of the undetected regions up to 150-Î¼m thicknesses. This achievement was quite significant considering the higher thickness test ratio. In future, further comparison shall be made using different material type.Â Â